THE ANALYSIS OF PARASITIC COMPLEXES OF LAKE FROG Pelophylax ridibundus Pallas, 1771 (ANURA, RANIDAE) DEPENDING ON POPULATION SPECIFICS OF THE HOST - A. V. BURAKOVA; V. L. VERSHININ; M. E. GREBENNIKOV (Российский паразитологический журнал)
The parasite fauna of lake frogs in the Ural region has been studied. 14 species of parasites belonging to Trematoda, Nematoda and Protozoa were found in the lake frog Pelophylax ridibundus in the South and Middle Ural. The parasitocenosis is characterized by a simplified structure while the number of infected animals increases with age. It was determined that the parasite species quantity in all age groups of P. ridibundus in the South Ural was higher than in the Middle Ural.